2009
DOI: 10.1530/rep-09-0158
|View full text |Cite
|
Sign up to set email alerts
|

Comparative aspects of implantation

Abstract: Uterine receptivity to implantation of blastocysts in mammals includes hatching from zona pellucida, precontact with uterine luminal (LE) and superficial glandular (sGE) epithelia and orientation of blastocyst, apposition between trophectoderm and uterine LE and sGE, adhesion of trophectoderm to uterine LE/sGE, and, in some species, limited or extensive invasion into the endometrial stroma and induction of decidualization of stromal cells. These peri-implantation events are prerequisites for pregnancy recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
291
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(305 citation statements)
references
References 112 publications
(118 reference statements)
5
291
2
7
Order By: Relevance
“…Around days 10 and 14 of pregnancy, embryos elongate and start to attach to the uterine wall. Further developed embryos will elongate quicker and get a larger implantation site (reviewed by Bazer et al 2009), which will provide an increased placental surface area (Stroband and Van der Lende, 1990). Foxcroft et al (2000) showed that substantial embryonic losses occur between day 26 and 44 of pregnancy.…”
mentioning
confidence: 99%
“…Around days 10 and 14 of pregnancy, embryos elongate and start to attach to the uterine wall. Further developed embryos will elongate quicker and get a larger implantation site (reviewed by Bazer et al 2009), which will provide an increased placental surface area (Stroband and Van der Lende, 1990). Foxcroft et al (2000) showed that substantial embryonic losses occur between day 26 and 44 of pregnancy.…”
mentioning
confidence: 99%
“…Like other ungulates (Perisodactyla and Artiodactyla), ruminant conceptuses remain freefloating after hatching from the zona pellucida (day 8-10 of pregnancy in cattle). Intimate contact with the uterus does not occur until on or after day 16 of pregnancy in cattle (Bazer et al 2009). This requires the development of a very different pregnancy signal, one that can function locally within the uterus instead of systemically.…”
Section: Interferons At the Placental-maternal Interfacementioning
confidence: 99%
“…In contrast to what occurs in primates and mice, in cattle, embryo implantation and placentation do not take place immediately after fertilisation; instead, the conceptus spends an extended period of time in the uterine lumen before fixing itself to the endometrium (BAZER et al, 2009). …”
Section: Introductionmentioning
confidence: 97%